Pertanggungjawaban Hukum Pelaku Usaha Konfeksi terhadap Pencemaran Sungai di Kota Denpasar - I Made Yudi Artana; I Nyoman Putu Budiartha; I Nyoman Sutama (Jurnal Analogi Hukum, 2019)
Water is one of the sources of life for all human beings. Water pollution is one of the heavy pollution that exists in Indonesia and waste sectors of industry are the dominant source of water pollution. In addition to the industrial sector, water pollution also posed in other sectors such as mining, agriculture and households. A result of water pollution is decreasing levels of water quality that can be utilized by humans. Water pollution occurs because there are some factories ignoring the material the rest of the production process of the waste to be processed perfectly on a waste management Unit (UPL), so the waste materials still contain compounds that are toxic (toxic compounds) and the cause of death. Then arise problems about setting up the implementation of the business license and can be rivaled river pollution legal liability by businessmen due to the waste of time it rivaled in Denpasar. Research methods in use empirical method such as approach legal sociology are analyzed using qualitative analysis techniques with good by the primary and secondary data sources and use interview techniques, observation, inventory and location determination. In the implementation of the permit, it shall follow the procedure, it rivaled efforts and implementing conditions and accountable through the means and the completion of which has been determined. Recommendations that can be given is that rivaled any attempt to understand the procedure of making the permission as well as understand the reason and implement applicable provisions, according to law, which rivaled both have done the water pollution of the river can be accountable for his deeds and take better care of the environment.